2 - Ndorobo Notions of Relationship with Other - Shelley Ashdown (African Sociological Review, 2015)
Among the Maa-speaking Ndorobo people on the southern Mau escarpment in Kenya, basic assumptions concerning Other are foundational for how an individual interacts with all that is outside of Self.1 In the course of field research in the Ndorobo homeland, three categories of significant Other were distinguished in Ndorobo world view.2 In this article these three Ndorobo categories of Other will be discussed with particular attention given to how these categories govern notions of relationship between Ndorobo and their classifications of Other. Classificatory distinctions are made between relationships of an individual Ndorobo with: (1) community Other (community in-group), (2) earthly Other (ethnic out-groups), and (3) supernatural Other (spirit beings).